(3EUdGM GdefWbs - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3CNHQfG CHh HcQ bGd CHh jhSa gPG HGH aYd haYd HGNJdGa GdeYfi GdMed eG cGf ai HWf , Ch Ydi QCS TLQI , hLeYI CMeGd hGdMed eG Med Ydi XgQ Ch Ydi QCS s
(3BNQgG (B:s
(3hGdOQLI WGFQ CShO HGWf GdLfGMjf hGdPcQ GdQHY eG fJL ai GdQHjY hGdMQH NOYI Je cJGH GdefWb HMeO Gddg s
(3HgG BKGQ JbWjYs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
Keywords: (3GddZIs